"Post-Gezi Islamic Theology: Intersectional Islamic Feminism in Turkey". Issue 2 (August 2016) - Dorroll, Philip
Abstract: The legacy of the 2013 Gezi Park protests has been controversial and its impact on Turkish politics difficult to assess. At the same time, there has been little reflection on contemporary Islamic feminist thinking in English sources. This essay argues that one important political and intellectual legacy of the Gezi movement has been the development of certain intersectional discourses in Islamic feminism in Turkey, whereby the shared experience of marginalization felt by pious Muslims, women, ethnic and religious minorities, and the LGBTIQ community has begun to broaden and complicate the scope of Islamic feminist discussions of liberation and social justice. By delineating and linking some important connecting threads of Islamic feminist theological thought in Turkey of the past 30 years, this essay will attempt to summarize key developments in the history of Islamic feminism in contemporary Turkey, demonstrating how they have led to new strands of intersectional feminist thinking in the post-Gezi era of Turkish politics.